US preschoolers' trust of and learning from media characters. Issue 3 (2nd July 2016) - Schlesinger, Molly A.; Flynn, Rachel M.; Richert, Rebekah A.
Abstract: The current study examined the relations between children's perceptions of character social realism, identification with characters, trust of characters as knowledgeable informants, and learning from media characters. Thirty-six 3½- to 6-year-old children watched a short clip of an animated educational television program about a preschool-aged boy who enjoys learning about science. Participants provided ratings of the character's social realism, their identification with the character, and their trust in the character as a knowledgeable informant. Participants were asked to solve problems based on information in the video clip. Findings revealed character trust was the strongest indicator of learning from the character. Results are discussed in the context of the different factors that influence learning from curriculum-based media for young children.